Fintech, macroprudential policies and bank risk: Evidence from China - Mohammad Abedin (International Review of Financial Analysis, 2023)
We explore the relationship between fintech, macroprudential policies, and commercial bank risk-taking. Based on system generalized method of moment modeling on a panel data of 114 commercial banks in China from 2013 to 2020, results show that there are functional differences in the impact of fintech on bank risk-taking. Payment and settlement technology (PST), capital raising technology (CRT) and investment management technology (IMT) are positively correlated with bank risk-taking. In contrast, market facility technology (MFT) negatively correlates with bank risk-taking. We also find that macroprudential policies weaken the promotion effect of CRT on bank risk-taking and strengthen the inhibition effect of MFT on bank risk-taking while having no significant moderating effect on PST and bank risk, IMT and bank risk. Further, the micro characteristics of banks (capital adequacy ratio, asset scale, liquidity level) affects the moderating strength of macroprudential policies. Various robustness tests confirm our conclusions.